Financial reporting in tabung masjid management driven by in Malaysia - Sarif, Suhaimi Mhd; Zakariyah, Luqman; Mohd Noor, Azman (The Islamic Cultural Centre London, 2018)
Financial reporting is an essential document that reflects the financial strength and capability of organizations. As a public place of worship, mosques or masājid in Malaysia are fully governed by State Religious Departments. Any activity requires written consent from the State Religious Authority including Tabung Masjid. Tabung Masjid management of mosques is regulated by state religious administrative law. Conventional approaches require compliance in fund collection and management for Tabung Masjid would remain ideas only if not operating with contemporary methods. The study argues that the compliance approach is necessary at the operation level but not at the corporate level. A case study method on a few selected mosques found that the finance committee has no choice but to abide by the regulation. In the meantime, there is a need to use of an innovative way through specific fund raising to address social issues. The study recommends the Tabung Masjid collection and management to be used as creative way of increasing the value of the fund within the Sharī‛ah compliant spirit.